Carcinoma de células acinares de parótida con patrón folicular - Serrú Estévez, Anibal Lázaro; Guevara Olazabal, Frank; Martin Suárez, Yulia Esther (Revista Cubana de Otorrinolaringología y Cirugía de Cabeza y Cuello, 2021)
Introduction: Acinar carcinoma of the salivary glands is a low-grade tumor of malignancy that ranges 1-6% of malignant tumors of the salivary glands in general. The follicular pattern is the rarest, it constitutes approximately 5% of acinar carcinomas. Few cases have been reported in the literature worldwide. Objective: To report the case of a patient with a recurrent parotid tumor. Clinical case report: This a male patient, black skin, of 54 years of age, with no history of chronic diseases, who came to the consultation for a left parotid tumor with a history of having been treated surgically in 2008 and then in 2015, when he had a recurrence of said lesion. Conclusions: Although the follicular pattern found is the rarest among acinar cell carcinomas worldwide, the combined use of fine needle aspiration biopsy with clinical and radiological evaluation can reduce diagnostic errors.